Optochemically Responsive 2D Nanosheets of a 3D Metal–Organic Framework Material. Issue 27 (10th May 2017) - Chaudhari, Abhijeet K.; Kim, Ha Jin; Han, Intaek; Tan, Jin‐Chong
Abstract : Outstanding functional tunability underpinning metal–organic framework (MOF) confers a versatile platform to contrive next‐generation chemical sensors, optoelectronics, energy harvesters, and converters. A rare exemplar of a porous 2D nanosheet material constructed from an extended 3D MOF structure is reported. A rapid supramolecular self‐assembly methodology at ambient conditions to synthesize readily exfoliatable MOF nanosheets, functionalized in situ by adopting the guest@MOF (host) strategy, is developed. Nanoscale confinement of light‐emitting molecules (as functional guest) inside the MOF pores generates unusual combination of optical, electronic, and chemical properties, arising from the strong host–guest coupling effects. Highly promising photonics‐based chemical sensing opened up by the new guest@MOF composite systems is shown. By harnessing host–guest optochemical interactions of functionalized MOF nanosheets, detection of an extensive range of volatile organic compounds and small molecules important for many practical applications has been accomplished. Abstract : A rapid supramolecular method to synthesize the "OX‐1" (Oxford University‐1) nanosheet metal–organic framework (MOF), functionalized adopting the guest@MOF strategy, is reported. Nanoscale confinement of light‐emitting guest molecules in the OX‐1 pores yields remarkable optical, electronic, and chemical properties. Harnessing reversible host–guest interactions, photochemical sensing of volatile organic compounds and small molecules important for many practical applications is demonstrated.